The Influence of Promotion, Price Perception and Product Quality on Purchasing Decisions: Mediation of Brand Image and Moderation of Word of Mouth Consumers of SMEs in Kampung Tahu Kediri - Reza, Osyta Chrisdianti Mei; Ambarwati , Diana; Munawaroh , Nuril Aulia (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of promotion, price perception, and product quality on purchasing decisions, with brand image as a mediator and word of mouth (WOM) as a moderator, in MSMEs at Kampung Tahu Kediri. Using SEM-PLS and 384 respondents, results reveal that promotion and product quality significantly influence purchasing decisions, while price perception does not. Brand image mediates the relationship between the three variables and purchasing decisions. WOM positively affects purchasing decisions and moderates the effect of price perception, but not promotion or product quality. Findings offer insights for enhancing MSME marketing strategies.